Relating to Responsibility : Essays in Honour of Tony Honor on his 80th Birthday. - Cane, Peter (Hart Pub., 2001)
The essays in this volume, written by eight of the world's leading legal theorists and philosophers, began life as papers presented at seminars (held in Canberra and New York) devoted to the ideas of Tony Honor, who is one of the most important legal thinkers of his generation.